Cancer drugs and the glomerulus. Issue 2 (June 2018) - Shah, Hitesh H; Uppal, Nupur N; Perazella, Mark A
Several chemotherapeutics including novel immunotherapies and targeted therapies have recently been approved for the treatment of various cancers. Several nephrotoxicities secondary to treatment with chemotherapeutics have been described in patients with cancer. Acute kidney injury from acute tubular necrosis and acute interstitial nephritis is commonly reported nephrotoxicities following treatment with cancer drugs. Although less common, several glomerular lesions include minimal change disease, collapsing and non-collapsing focal segmental glomerulosclerosis secondary to chemotherapy-related podocyte injury have been reported in the literature. In addition to conventional chemotherapeutics, several novel cancer drugs including immune point check inhibitors, anti-vascular endothelial growth factor inhibitors, and tyrosine kinase inhibitors have also been associated with various glomerular lesions. While the occurrence of glomerular toxicities related to cancer drugs is less common than tubular injury, failure to recognize these associations may lead to poor renal outcome. In this article, we review several chemotherapy-related glomerular diseases including thrombotic microangiopathy.